Power and thermal constraints of modern system-on-a-chip computer. Issue 12 (December 2015) - Rotem, Efraim; Ginosar, Ran; Mendelson, Avi; Weiser, Uri C.
Abstract: Junction temperature has been considered the main physical constraint for high end processors. Recent trends in form-factors and the increased focus on thin and light systems such as Ultra Book, tablet computers and smartphones, shift the focus away from managing and controlling junction temperature. Ergonomic considerations and power delivery are becoming the limiters of high computational density. In this paper we describe the major physical constraints, design considerations and modern power and thermal management techniques and demonstrate them on an Intel ® Core™ i7 system.